Transport & atmospheric chemistry near the equator-Atlantic : GTE Trace-A : NASA-INPE. (Atmospheric Sciences Data Center, NASA Langley Research Center, 2000)
A comprehensive investigation of the chemical composition, transport, and chemistry of the atmosphere in the south Atlantic Ocean and the adjacent South American and African continents. Information on radiation, clouds, aerosols, and tropospheric chemistry.